Towards long lasting zirconia-based composites for dental implants. Part I: Innovative synthesis, microstructural characterization and in vitro stability. (May 2015) - Palmero, Paola; Fornabaio, Marta; Montanaro, Laura; Reveron, Helen; Esnouf, Claude; Chevalier, Jérôme
Abstract: In order to fulfill the clinical requirements for strong, tough and stable ceramics used in dental applications, we designed and developed innovative zirconia-based composites, in which equiaxial α-Al2 O3 and elongated SrAl12 O19 phases are dispersed in a ceria-stabilized zirconia matrix. The composite powders were prepared by an innovative surface coating route, in which commercial zirconia powders were coated by inorganic precursors of the second phases, which crystallize on the zirconia particles surface under proper thermal treatment. Samples containing four different ceria contents (in the range 10.0–11.5 mol%) were prepared by carefully tailoring the amount of the cerium precursor during the elaboration process. Slip cast green bodies were sintered at 1450 °C for 1 h, leading to fully dense materials. Characterization of composites by SEM and TEM analyses showed highly homogeneous microstructures with an even distribution of both equiaxial and elongated-shape grains inside a very fine zirconia matrix. Ce content plays a major role on aging kinetics, and should be carefully controlled: sample with 10 mol% of ceria were transformable, whereas above 10.5 mol% there is negligible or no transformation during autoclave treatment. Thus, in this paper we show the potential of the innovative surface coating route, which allows a perfect tailoring of the microstructural, morphological and compositional features of the composites; moreover, its processing costs and environmental impacts are limited, which is beneficial for further scale-up and real use in the biomedical field.